THE DEVELOPMENT OF A HIGH‐RESOLUTION MASS SPECTROMETRY METHOD FOR ULTRA‐TRACE ANALYSIS OF CHLORINATED DIOXINS IN ENVIRONMENTAL AND BIOLOGICAL SAMPLES INCLUDING VIET NAM ERA VETERANS. Issue 3 (12th June 2020) - Lay, Jackson O.; Liyanage, Rohana; Gidden, Jennifer A.
Abstract : Chlorinated dioxins are labeled and recognized by both the World Health Organization and the United Nations Environmental Programme (UNEP) as "persistent organic pollutants". Their potential for high toxicity is one of the primary factors behind intense public and regulatory scrutiny and the need to measure the compounds at very low limits, specifically the isomer 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (2, 3, 7, 8‐TCDD). This article highlights the early mass spectrometry methods to investigate, detect, confirm, and quantify chlorinated dioxins and the initial applications involving human biomonitoring, as attempts were made to attribute health effects to TCDD exposure. This effort represented a complex and difficult scientific response to the pressing need to investigate expected exposures and alleged subsequent medical effects, which in the case of the Viet Nam veterans was being attempted a decade or more after their exposure. It is noteworthy that this method and its development touched on delicate issues involving human subjects, war veterans, environmental contamination, and was difficult not only scientifically, but for ethical and political reasons as well. Stable‐isotope dilution with analysis by gas chromatography/high‐resolution mass spectrometry (GC/HRMS) became the method of choice because of its ability to monitor characteristic ions and isotope ratios to quantify and qualify/confirm the analyte in the presence of coextracting and coeluting interferences at these low levels with the highest possible confidence. This method was rigorously tested and validated before it was used to discover and monitor levels in the environment and in various populations at then unprecedented low levels. These early studies demonstrated the feasibility of monitoring dioxins in humans even decades after exposure, and led to the detection of 2, 3, 7, 8‐TCDD in the general population as well as specific overexposed populations. These studies also provided strong evidence regarding the origins of the 2, 3, 7, 8‐isomer in the environment. © 2020 John Wiley & Sons Ltd. Mass Spec Rev